Surface roughness and hardness of some dental ceramics and restorative resins - (:unkn) unknown (Trans Tech Publications Ltd, 2004)
The aim of this study was to compare the surface hardness and roughness of seven composite resins (Ælite LS(Æ), Clearfil Poto Posterior(CPP), SureFil (SF), Tetric Ceram (TC), Artglass (AG), Admira (AD), Estenia (ES)) and two ceramic materials (Vitadur Alfa (VA), Finesse(FI)). The composite speciemens were cured in cylindirical brass molds (4mm in diameter and 2 mm in depth) against glass according to manufacturers' directions and polished. The ceramic specimens were prepared in same diameters, glazed. Hardness was determined at two different sites on one side specimens and the mean value was calculated as Vicker's Hardness Numbers (VHN). Surface roughness (SR) was measured tree times as Ra (μm) on each specimen and mean roughness values were obtained. For statistical analyses Mann Whitney U test was used. Surface roughness values of CPP, ES were very close to that of VA. Their surface roughness values were significantly higher than other materials. VHN of ES and AG were significantly lower than that of two ceramic materials. The surface hardness of ES was significantly harder than composite resins (P<0.05).
Keywords: Composite resin and ceramic; Hardness; Roughness